ETIKA YOGA DALAM KAKAWIN ARJUNA WIWAHA - I Made Soma Naryana; I Made Adi Brahman; Made G. Juniartha (UHN IGB Sugriwa Denpasar, 2023)
Kakawin Arjuna Wiwaha written by Mpu Kanwa is a literary work that requires life values. The practice of tapa or yoga performed by Arjuna in the text of the Kakawin Arjuna Wiwaha has become a guideline for how yoga should be practiced by yoga practitioners. Furthermore, this research tries to explore the axiology of yoga, especially about the ethical values ​​of yoga contained in the text of Kakawin Arjuna Wiwaha. The theory used to analyze these problems is the hermeneutic theory. The method used in this study includes: this type of research is qualitative research, the data is collected through literature study and document study techniques. The data were analyzed by interpreting the qualitative data. Axiological studies, especially the ethical values ​​of yoga that can be explored in the text of Kakawin Arjuna Wiwaha include: the value of success in in carrying out obligations (swadharma), the value of self-control, the value of detachment from sensory objects, and the value of firmness and resistance to temptation.